CAPITAL ASSET PRICING MODEL IN FORECASTING THE EXPECTED RETURN: THEORY AND EVIDENCE - Ika Pratiwi Simbolon (President University Press, 2017)
This paper is made to investigate the theories and evidences related to the evolution of the Capital Asset Pricing Model (CAPM). The previous studies examined the single factor model, CAPM and Theory of Arbitrage, conditional CAPM on positive and negative market premium, CAPM with higher skewness and kurtosis, and also CAPM with higher size. This paper finds that there’re so many previous researchers investigated the robustness of the Capital Asset Pricing Model. The return expectation from investor cannot be explained by the single factor, namely systematic risk (beta). Hence, there’re various models that have been developed and investigated to project the return expectation in capital market.